Colombia’s mining renaissance a brief discussion on governance, development and policy making (2012)
This research paper aims to formulate a comprehensive foreign investment policy towards Latin America and Colombia in commodities production like oil, gas, gold, silver, industrial metals, and other less known but valuable minerals, such as ‘exotic’ minerals like coltan (columbium or niobium and tantalum) whose elements are considered ‘critical’ for hi-tech industries i.e. defence, aerospace and communications due to their particular physical and chemical properties. Particularly, the paper studies the parttern of FDI inflows to Colombia in recent years and the results of the investment promotion measures taken by the Colombian government especially in the mining sector. An important policy convergence is found between Colombia and South Korea in those areas, that can be exploited to mutual advantage in a Free Trade Agreement framework being concluded between the two countries. However, the policy convergence still needs to be tested into policy action.